Tinjauan Kinerja Bundaran Tiga Lengan Dengan Simulasi Karakteristik Arus Lalu Lintas Pada Bundaran Patung Tololiu Kota Tomohon - Wuwung, Victorie Harly; Waani, Joice E.; Jansen, Freddy (JURNAL ILMIAH MEDIA ENGINEERING, 2018)
Transportation system in a region, act as a vein and also tools to measure the development progress of that particular region, therefore the system growth is usually corelates the growth of other sectors in society, such as economy, social, culture, politics and citizenship, thus the transportation system becomes a deciding factor of a regional growth. A good transportation system is able to ensure the mobility of goods, service and people in an effective, efficient, safe, comfortable integrated andsustainable. One way to achive that is through traffic control, in which the Tololiu Roundabout in Tomohon city as a crossing point that connects Tomohon city and other administrative regions in North Sulawesi, whereas the current roundabout requires data to be able to be adapted with theincreasing regional growth.      The purpose of this research is expected to describe the existing Level of Service (LoS) of the roundabout and predicts the future condition up to 2022 and able to be used as an accountable data for future growth of Tomohon city. The method applied in this research are literature study, primary and secondary data collection, data analysis using MKJI 1997 method and software simulation using AutoCAD 2017, Microsoft Excel2016 and Synchro Studio 9,0.      AutoCAD used to simplify the roundabout geometric analysis, Microsoft Excel used to calculate the MKJI 1997 RWEAV-I and RWEAV-II form and Synchro studio 9,0 used to create a real-time simulation of the traffic characteritics in the field of study.      The result of the MKJI 1997 analysis coupled with the regional demografic data to predict the future condition up to 2022 shows that the Degree of Saturation (DS), exceeded the boundary threshold of 0,75 in the year of 2019 and so is adviced to apply a geometric and/or volume engineered solution. The result of the Synchro Studio 9,0 simulation shows B grade LoS for the existing data of 2015, but exceeded the boundary threshold of DS in US HCM 2010 method in the following year.The different result by the two methods analyses are due to the different parameters incorporated in both method where the US HCM 2010 in Synchro 9,0 is leaning on Delay Control (and more complex parameters) and the MKJI 1997 mothod rely on the Volume and Capacity. Either way, the study and analysis show that the Tololiu Roundabout in Tomohon city is in need of re-engineering in order to adapt to the future regional growth by applying geometric road widening, no-parking zone, volume divertion through the two minors approach available and also a social education of the roundabout rules and regulation coupled with the good-will of the government to provide the neccesarry facility and tools for the roundabout. Keywords: Tololiu Roundabout, Level of Service (LoS), Degree of Saturation (DS), US HCM, MKJI.